Licensing of Seed Treatment Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-147, a 2-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use pesticides to seeds in Florida. Published by the UF Pesticide Information Office, February 2007.